2019
DOI: 10.1128/jvi.00413-19
|View full text |Cite
|
Sign up to set email alerts
|

Pentosan Polysulfate Demonstrates Anti-human T-Cell Leukemia Virus Type 1 ActivitiesIn VitroandIn Vivo

Abstract: Human T-cell leukemia virus type 1 (HTLV-1) infection causes T-cell leukemia and inflammatory diseases, most notably including HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP). The underlying mechanism for the pathogenesis of HAM/TSP remains unclear. According to a recent clinical trial, a humanized antibody that targets CCR4 ϩ cells ameliorates inflammation by reducing the number of infected cells in the central nervous system; this result suggests that the transmigration of HTLV-1-infected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 77 publications
0
8
0
Order By: Relevance
“…For the endogenous interaction between YAP and p65, ATL cell lysate was incubated with anti-YAP antibody (Cell Signaling Technology) or anti-mouse immunoglobulin G (IgG) (Santa Cruz Biotechnology), and the following procedures were the same as described above in 293T cells. Other antibodies used were as follows: anti-FLAG M2, anti-HA, anti–c-Myc (Sigma-Aldrich), anti-p65, anti–phospho-YAP (Ser127), anti–phospho-YAP (Ser381), anti-GAPDH (Cell Signaling Technology), and anti-Tax was used as previously described ( 51 ).…”
Section: Methodsmentioning
confidence: 99%
“…For the endogenous interaction between YAP and p65, ATL cell lysate was incubated with anti-YAP antibody (Cell Signaling Technology) or anti-mouse immunoglobulin G (IgG) (Santa Cruz Biotechnology), and the following procedures were the same as described above in 293T cells. Other antibodies used were as follows: anti-FLAG M2, anti-HA, anti–c-Myc (Sigma-Aldrich), anti-p65, anti–phospho-YAP (Ser127), anti–phospho-YAP (Ser381), anti-GAPDH (Cell Signaling Technology), and anti-Tax was used as previously described ( 51 ).…”
Section: Methodsmentioning
confidence: 99%
“…Cells were then switched to serum-free Trophoblast Medium for 24 hours before incubation in the same medium with or without human recombinant IGF-1 (PeproTech) (20 or 200 ng/mL) for 24 hours, as previously described (46). To infect placental cells with HTLV-1, VTs, VMFs, and PVECs were cocultured with lethally irradiated HTLV-1-producing MT-2 cells as previously reported (47). On the next day of cocultivation, the cells were thoroughly washed with PBS to remove residual MT-2 cells.…”
Section: Methodsmentioning
confidence: 99%
“…We examined whether placental cells infected with HTLV-1 expressed viral antigens. Considering that HTLV-1 infection is spread by cell-to-cell transmission, a coculture model of HTLV-1-producing cells and target primary cells was employed (47). Target VTs, VMFs, and PVECs were cocultured with HTLV-1producing cells ( Figure 6A), and the expression level of viral envelope glycoprotein on the surface of the target cells was analyzed by flow cytometry.…”
Section: 7mentioning
confidence: 99%
“…Early inhibition of viral attachment and entry represents a key advantage in acute disease management, and several antiviral drugs targeting these mechanisms have been developed and tested ( 10 , 41 , 42 ). PPS has been shown to inhibit human T-lymphotropic virus 1 (HTLV-1) replication in vitro ( 43 ), and recent studies indicate that PPS inhibits SARS-CoV-2 infection in vitro by modifying the receptor binding domain of S1 protein ( 44 , 45 ). We found that at 8 dpi, viral titers in the lungs of mice infected with PR8 were not affected by PPS treatment, with no differences observed between infected mice treated with vehicle or with 3 mg/kg PPS.…”
Section: Discussionmentioning
confidence: 99%